2018
DOI: 10.17706/jsw.13.4.242-259
|View full text |Cite
|
Sign up to set email alerts
|

Effort Estimation across Mobile App Platforms using Agile Processes: A Systematic Literature Review

Abstract: Abstract:It is predicted that smartphone numbers will increase to 2.8B in 2018, up from around 2B in 2016. Moreover, revenue from application stores is predicted to reach $189B by 2020, up from $88.3B in 2016 1 . Software effort and size estimation are essential when it comes to project managers being able to manage and plan a project so as to prevent it from failing. The planning and development of mobile applications differs from other traditional software applications due to the characteristics of the mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 50 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…Software developers require effective effort estimation models to facilitate project planning and for the eventual successful implementation of the project [15]. If the effort estimations are accurate, they can contribute to the success of software development projects, while incorrect estimations can negatively affect companies' marketing and sales, leading to monetary losses [16]. Software project estimation involves the estimation of the effort, size, staffing, schedule (time) and cost involved in creating a unit of the software product [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…Software developers require effective effort estimation models to facilitate project planning and for the eventual successful implementation of the project [15]. If the effort estimations are accurate, they can contribute to the success of software development projects, while incorrect estimations can negatively affect companies' marketing and sales, leading to monetary losses [16]. Software project estimation involves the estimation of the effort, size, staffing, schedule (time) and cost involved in creating a unit of the software product [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…There exists a systematic literature review [14] which has provided an overview of the current state-ofthe-art for effort estimation techniques in mobile app development which use the Agile process. 21 papers were found among this literature; 13 of the 21 studies concerned the estimation size metrics and techniques in mobile app development, whereas 8 studies concerned the applicability of the Agile process in the development of mobile apps.…”
Section: Related Workmentioning
confidence: 99%
“…[13]. Another systematic literature review was conducted for the effort estimation techniques in mobile apps [14]; as a result, no previous studies were found regarding the state-of-practice to investigate and validate the suitability of existing estimation techniques which are used in the Agile process, such as Planning Poker, for mobile app development.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The initial development costs of mHealth apps can range from the thousands to the hundreds of thousands of dollars, with factors such as the number of screens, complexity of content (static or dynamic), and inclusion of media files (e.g. video), all contributing to higher costs [18,19]. Further, there are many non-trivial issues in the development and effective design of the components of mobile health systems currently being addressed by the mobile computing research community, such as energy efficiency, data management, human-computer interaction factors, and developing flexible and generic APIs to support health apps [20,21].…”
Section: Introductionmentioning
confidence: 99%